Особливості метаболізму вуглеводів в пагонах магнолієвих у зв’язку із зимостійкістю в умовах південного сходу України - Grigorenko, I.V.; Golovnya, Y.N.; Bessonova, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Cited herein is the data concerning the study of starch and sugars dynamics during autumn-winter-spring period in representatives of the Magnoliaceae family growing under the conditions of the South-East of Ukraine. The paper considers intertransition of carbohydrates during this period. The species specificity of seasonal variations of these indiced has been found out.